2016
DOI: 10.5812/jjm.41431
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Biofilm Production Capability and icaA/D Genes Among Staphylococci Isolates from Shiraz, Iran

Abstract: Background: Biofilm formation capacity is recognized as an important virulence factor in staphylococci that makes the organisms more resistant to antibiotics and host defenses. Objectives: This study aimed to determine the biofilm producing ability and presence of icaA/D genes in staphylococcal isolates obtained from different clinical specimens. Methods: This cross-sectional study was performed on a total of 151 staphylococcal isolates (79 Staphylococcus aureus and 72 S. epidermidis) obtained from different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Observed results happen to be the same as Delpozo and Patel Filho's findings [8,17]. In 2016, two different studies investigated clinical isolates of S. epidermidis collected from a private hospital in Tehran [18] and clinical isolates from Shiraz city [19]. Zalipour reported that in 81.9% of clinical isolates of S. epidermidis, ica Luci was observed [19].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Observed results happen to be the same as Delpozo and Patel Filho's findings [8,17]. In 2016, two different studies investigated clinical isolates of S. epidermidis collected from a private hospital in Tehran [18] and clinical isolates from Shiraz city [19]. Zalipour reported that in 81.9% of clinical isolates of S. epidermidis, ica Luci was observed [19].…”
Section: Discussionsupporting
confidence: 75%
“…In 2016, two different studies investigated clinical isolates of S. epidermidis collected from a private hospital in Tehran [18] and clinical isolates from Shiraz city [19]. Zalipour reported that in 81.9% of clinical isolates of S. epidermidis, ica Luci was observed [19]. Rahimi reported that 82% of the isolated strains were biofilm-formers and all of the biofilm former S. epidermidis isolates carried icaA, icaD, aap, and atlE genes [18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this fact, 33 patients (45.8%) had chronic dacryocystitis in our study, with S. epidermidis being the dominant bacterial species (7 patients: 21.2%), and thus, we suggest that based on the present study, chronic dacryocystitis could be a potential source of intraocular infections due to higher growth rates of S. epidermidis and E. aerogenes (20). Moreover, this finding may be because of significant biofilm-producing ability of staphylococci and their association with chronic and implanted medical devices infections [27].…”
Section: Discussionsupporting
confidence: 52%
“…Jain and Agarwal [ 28 ] reported a higher rate where 64% of staphylococcal intravascular isolates were biofilm producers by CRA method. Zalipour et al [ 29 ] reported that forty-three (54.4%) biofilm forming strains were found in clinical specimens in Iran by CRA assay. In the current study, seven (32%) isolates were strong biofilm formers and fifteen (68%) isolates were moderate biofilm formers.…”
Section: Discussionmentioning
confidence: 99%